Pengaruh Pengetahuan, Kualitas Pelayanan dan Tingkat Kepuasan terhadap Kepatuhan Wajib Pajak - hamid, ahmad; Sultraeni, Wiwin; Fitriadi, fitriadi; Breemer, Jacob (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2022)
This study aims to examine the effect of tax knowledge, service quality and satisfaction level on taxpayer compliance with e-filling users. The data in this study were obtained from taxpayers registered at the North Makassar KPP Pratama who were willing to become respondents. This study uses primary data by conducting direct research in the field by providing questionnaires/question sheets to 100 respondents. The data analysis method used is multiple linear regression analysis. The results showed that: partially, the variables of tax knowledge, service quality and satisfaction level had a positive and significant effect on taxpayer compliance with e-filling users.